Soymilk plant simulation to predict the formula of a new Hypothetical Product (2018)
Ideal Patterns reactors alteration by real reactor patterns, for better accuracy was done using industrial software: Aspen Plus and Hysys Version 7.1 to represent the batch real mixer and soymilk production system. Fluid package for properties prediction was chosen from the software list. A feed steam of 41,67 Kg/h (Soybean) was taken; mass fractions were given by element since the Soybean has a wide blend of substances which cannot be described as a unique compound formula. The elements were C, N, H, O, S, Na, K, Mg, Ca, Fe, P, and Cu. Final flow of 8,333 Kg/h was used to achieve the objective of this study: the elemental analysis method for the hypothetical new product prediction (based only in presence of Amino-acids and other macro and multiple substances). The macromolecules described here are the onset for new specific soymilk compounds such as the concluded on this study. Fulminic Acid Family compound and the protein analysis may correspond to new proteins which are not well-known such as the ones found in studies by the Hospital de Rhode Island in 2014. Presence of Fe and Cu in soybean was ascribed to the micronutrients that could be present in the soil of crop cultivation and in soybeans by absorption.